Two are better than one: volatility forecasting using multiplicative component GARCH‐MIDAS models - Conrad, Christian; Kleen, Onno (Journal of applied econometrics, 2020)
We examine the properties and forecast performance of multiplicative volatility specifications that belong to the class of generalized autoregressive conditional heteroskedasticity-mixed‐data sampling (GARCH‐MIDAS) models suggested in Engle, Ghysels, and Sohn (Review of Economics and Statistics, 2013, 95, 776–797).
First published: 02 November 2019
Gesehen am 18.01.2021